Types and peculiarities of home furniture of the Kazakh people - Baidabekov Әуез (Рroblems of engineering and professional education, 2022)
In the article types and features of furniture of the Kazakh people are considered and it is shown that our people pay great attention to the availability of such rich and diverse furniture, beauty and decoration. As a result of these studies, you can create and promote modern types of furniture.